Exploring Mathematics Learning Strategies of High-Scoring Group Students at Secondary-level - Khanal, Bishnu; Chhetri, Deb Bahadur (Interdisciplinary Issues in Education, 2024)
Students’ achievement in mathematics at school-level is significant concern in the context of Nepal. Various factors contribute to success and failure in mathematics with learning strategies adopted by the students being crucial element. This study explores the mathematics learning strategies employed by students who secure high core in mathematics and their motivating factors in the context of Nepal. The study employed an exploratory research design within the qualitative research framework, focusing on a select group of high-scoring students. Specifically, the research involved the investigation of only five students from the high-scoring cohort. Two times interview was utilized for data collection and thematic analysis was used for data analysis. Findings revealed that participants reported multiple strategies encompassing rigorous practice, self-regulated learning, and collaborative learning. Their persistent determination, drove by intrinsic motivation and aspirations for the future, emphasizes the crucial significance of positive attitudes in overcoming obstacles. Furthermore, the pivotal contributions of robust support systems from teachers, family, peer group emerged as influential motivational promoters. Highlighting customized instructional approaches and nurturing supportive learning environments show the potential to strengthen mathematics education and promote good achievement worldwide.